Pulmonary metastases in newly diagnosed hepatocellular carcinoma: a population-based retrospective study - Feng, Jincheng; He, Ying; Wan, Junhua; Chen, Zhishui (HPB, 2020)
Background - Hepatocellular carcinoma (HCC) is a major form of primary liver cancer with steadily increasing incidence for the decades, and has propensity to have extrahepatic metastases, especially pulmonary metastases (PM). This study aimed to investigate temporal incidence trends, treatment, and survival of patients with HCCPM. - Methods - Patients with HCCPM were retrospectively reviewed from 2010 to 2016 in US National Cancer Institute (NCI) Surveillance, Epidemiology, and End Results registry (SEER). - Results - 2242 patients with HCCPM were identified. Overall HCCPM incidence did not change from 2010 to 2016, with an annual percent change (APC) of 0.87% (95% CI = −2.50%-4.35%, P = 0.542). Similar incidence trends patterns were found in subgroup analyses of sex, age, and race. 1-year observed survival for HCCPM was 10.8% (95%CI = 8.9%-12.8%) and relative survival was 11.0% (95%CI = 9.1%-13.1%). Better outcomes were noted among patients who underwent liver-directed surgery, those who treated with chemotherapy, and those who received radiation. - Conclusions - The incidence of HCCPM does not increase with the increasing incidence of HCC. Patients with HCCPM have a dismal prognosis with low survival rates. Liver-directed surgery, use of chemotherapy, and radiation may be associated with improved outcomes.